Practical programming an introduction to computer science using Python 3.6 - Gries, Paul; Campbell, Jennifer; Montojo, Jason (Pragmatic Bookshelf, 2017)
Annotation
Place of publication from publisher's Web site. - Includes bibliographical references. - Online resource; title from title page (Safari, viewed February 16, 2018)
Keywords: Python (Computer program language); Computer programming; Computer science; Electronic Data Processing; Python (Langage de programmation); Programmation (Informatique); Informatique; computer programming